THE INFLUENCE OF PRODUCT QUALITY AND PROMOTION ON PURCHASE DECISIONS AT LARISSA BABYMART UJUNGPANGKAH GRESIK - Farida, Nur; Shofiyah, Ainin (SYNTIFIC, 2023)
Background. Product quality is a determining component in purchasing decisions. Apart from product quality, another variable that influences purchasing decisions is promotion. Promotion is one of the determining factors in event purchasing decisions. Whatever the nature of an item, assuming the buyer never knows or does not know whether the item will be of value to the buyer, the customer will not be interested in getting it, meaning that purchasing decisions also pay attention to this. Research Purpose. To frame the buyer's disposition in the face of all the data and take reactions as to what goods to buy. Research Method. This is an illustrative form with a quantitative methodology. This research strategy can be interpreted as an exploitation technique from a positivism perspective, which is used to look at populations or tests which can later be used for research text components, describing them quantitatively or measurably. information with the intention of testing the speculations made. Findings. Product quality to a certain extent influences purchasing decisions, while promotions to a certain extent greatly influence decisions and product quality and promotions also influence purchasing decisions. Conclusion. The idea of Larissa Babymart scientists is to further improve advertising through timely virtual entertainment according to product quality to improve purchasing decisions.